(untitled) - Severin, Werner J. (New York, 2001)
The Fifth Edition addresses ongoing changes in mass communications and new developments in mass communications theory. The book also applies communication theories to the mass media with current examples from journalism, broadcasting, advertising and public relations to clarify the concepts. A new chapter on cyber communications explores the influential new medium, using discussions of mediamorphosis, hypertext, multimedia, interface design, Internet addiction and Internet dependency. An extensively rewritten chapter on media chains and conglomerates addresses key developments in the field. The book also includes unique coverage of media uses and institutions, meant as an alternative way to think about mass communication. For readers interested in exploring mass communication theory.
Keywords: Mass media,Communication